Nursing Workload And Its Impact On Patient Outcomes In Saudi Arabia (The Review of Diabetic Studies, 2024)
Introduction: The Kingdom of Saudi Arabia (KSA) is experiencing a fast transformation in the health sector due to the Saudi Vision 2030 that seeks to enhance the quality of care and patient safety. The hub of this change is the nursing workforce which is grappling with such problems as high dependency on expatriate workers and continuous nursing shortage. Nursing workload- both by the objective ratio of patients to nurses, and the perceived demands- has been identified to be a key determinant of clinical outcomes.Study Objective: The major goal of this systematic review is to collate evidence surrounding the association between nurse workload and patient outcomes in Saudi Arabian hospitals by analyzing published data for nurse-to-patient ratios and workload perceptions across different clinical environments (i.e. CCUICM, Med - Surg, and PHCs) in Saudi Arabia.Methodology: This systematic review was done according to the PRISMA guidelines. Primary studies to be included in the research were searched in electronic databases, such as PubMed, CINAHL, and Scopus, along with the Saudi Digital Library, published in the 2015-2025 period. Key words were based on nursing workload, patient outcomes and Saudi Arabia. The inclusion criteria were that the studies had to be carried out in KSA and should furnish empirical information regarding the correlation between the nurse requirements and patient-associated safety or quality indicators. Conclusion: The results show that there is a statistically significant correlation between high nursing workload and patient outcomes compromised in Saudi Arabia. Another major predictor of medication administration errors and Healthcare-Associated Infections (HAIs) was consistently referred to increased workload. Moreover, excessive workload is one of the key obstacles to accomplishing the necessary nursing tasks, and it results in Missed Nursing Care, which has a negative influence on the recovery and satisfaction of patients. The review concludes that the existing staffing models in KSA need to change to acuity based staffing and focus on retention of experienced staff to avoid the risks of excessive workloads.